STUDY LITERATURE REVIEW FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI REMAJA PUTRI - Tria Nopi Herdiani; Venty HS Manujung; Violita Siska Mutiara (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
The cause of nutritional problems in young women can be caused by a strict diet (which causes adolescents to not get a balanced and nutritious diet) and poor eating habits. This study aims to determine the factors associated with the nutritional status of adolescent girls in 2020. This study uses the literature review method by using the inclusion and exclusion criteria. Keywords used in this literature search include: "nutritional status of adolescent girls, balanced nutritional knowledge, physical activity, body image or body image". The results were obtained: (1) from five literatures examining the variables of physical activity 3 studies with the results there was a significant relationship between physical activity and nutritional status; (2) from four literatures examining body image variables, 3 studies with the results found a significant relationship between body image and nutritional status; (3) of the three literature studies that examined knowledge, 2 studies stated there was a relationship of knowledge with nutritional status. It is recommended that schools work together with Puskesmas nutrition officers to re-activate monitoring of the nutritional status of students, provide periodic socialization about patterns of physical activity and balanced nutrition and good eating patterns. In addition, health promotion to students also emphasizes obesity. Keywords:physical activity, body image, knowledge, nutritional status of adolescent girls